24th “Nantes Actualités en Transplantation” and 4th “LabEx Immunotherapy-Graft-Oncology” NAT and IGO Joint Meeting “New Horizons in Immunotherapy” - Joalland, Noémie; Ducoin, Kathleen; Cadiou, Gwenann; Rabu, Catherine; Guillonneau, Carole (Frontiers in Immunology, 2021)
The 24th edition of the annual NAT conference (Nantes Actualités Transplantation) and the 4th edition of the biennial LabEx IGO meeting (Immunotherapy Graft Oncology) were held jointly around a common theme: "New horizons in immunotherapy", on May 31st and June 1st 2021 to highlight new findings in the fields of transplantation, autoimmunity and cancer.